Persepsi Mahasiswa terhadap Dosen dalam Mengajar di Fakultas llmu Komunikasi Universitas Prof. Dr. Moestopo (Beragama) - Sunarto, Sunarto; Syahudi, Giman; Erland, Radja (Universitas Prof. Dr. Moestopo (Beragama), 2008)
This research of background overshadow by existence of some problems of arisingout in course of study like for example less obedient the lecturer to discipline teach and less precisely instruction method used by some lecturer, this matter have opportunity to generate impact of student, by unfavourable ways of lecturer in teaching to generate ugly perception among student to lecturer,so that in the end will affect at degradation of education quality.Pursuant to the background hence problems which lifted in this research is